Explantation of KAMRA Corneal Inlay: 10-Year Occurrence and Visual Outcome Analysis - Moshirfar M; Lau CK; Chartrand NA; Parsons MT; Stapley S; Bundogji N; Ronquillo YC; Linn SH; Hoopes PC (Clinical Ophthalmology, 2022)
Majid Moshirfar,1– 3 Chap-Kay Lau,4 Nicholas A Chartrand,4 Mark T Parsons,4 Seth Stapley,5 Nour Bundogji,2 Yasmyne C Ronquillo,1 Steven H Linn,1 Phillip C Hoopes1 1Hoopes Vision Research Center, Hoopes Vision, Draper, UT, USA; 2John A. Moran Eye Center, University of Utah School of Medicine, Salt Lake City, UT, USA; 3Utah Lions Eye Bank, Murray, UT, USA; 4University of Arizona, College of Medicine-Phoenix, Phoenix, AZ, USA; 5Arizona College of Osteopathic Medicine, Midwestern University, Glendale, AZ, USACorrespondence: Majid Moshirfar, Medical Director Hoopes Vision Research Center, Hoopes Vision Research Center, 11820 S. State St. #200, Draper, UT, 84020, USA, Tel +1 801-568-0200, Fax +1 801-563-0200, Email cornea2020@me.comPurpose: To evaluate 10 years of KAMRA corneal inlay explantation and associated visual outcomes.Patients and Methods: Single-site retrospective chart review of 22 cases of AcuFocus KAMRA Inlay (ACI7000PDT) explantation (range 1 week– 1 year). Uncorrected distance visual acuity (UDVA), uncorrected near visual acuity (UNVA), corrected distance visual acuity (CDVA), and manifest refraction at 1 day, 1 week, 1 month, 3 months, 6 months, and 1 year post-explantation were reviewed.Results: The explantation rate was 8.2% across 10 years. All patients underwent KAMRA explantation due to dissatisfaction with their vision including blurry near vision, impaired night vision, decreased vision in dim lighting, streaks or halos, haze, and double vision. Mean UDVA pre-implant was − 0.01± 0.13 logMAR (logarithm of the minimal angle of resolution), 0.30± 0.22 logMAR pre-explant, and 0.16± 0.15 logMAR post-explant (n=20). Mean UNVA pre-implant was 0.37± 0.09 logMAR, 0.38± 0.13 logMAR pre-explant, and 0.42± 0.21 logMAR post-explant (n=20). Mean CDVA pre-implant was − 0.01± 0.04 logMAR and 0.05± 0.11 logMAR post-explant (n=17). Mean CDVA pre-explant was 0.04± 0.07 logMAR and 0.04± 0.11 logMAR post-explant (n=19). Significant differences were observed between pre-implant and post-explant UDVA (p=0.009), and between pre-explant and post-explant UDVA (p=0.02). All patients (100%) had 20/20 or better CDVA pre-implant but decreased to 73.7% post-explant. Sixty percent (12/20) of the patients lost UDVA Snellen acuity lines post-explant. MRSE was − 0.31± 0.29 D pre-implant and +0.26± 0.77 D post-explant (p=0.007) with note of a hyperopic shift. The hyperopic shift in 31.6% (6/19) of patients did not resolve after explantation. Post-explant residual corneal haze occurred in 72.7% (16/22) of patients.Conclusion: Although the KAMRA corneal inlay is a removable device, patients may experience residual corneal haze, hyperopic shift, and deficits in UDVA after explantation compared to pre-implantation UDVA.Keywords: presbyopia, cornea, small aperture inlay, KAMRA, explantation